Similar results for face mask versus mouthpiece during incremental exercise to exhaustion - Wagner, D. R.; Clark, N. W. (Journal of Sports Sciences, 2016)
Investigations in the 1990s evaluated the influence of breathing assemblies on respiratory variables at rest and during exercise; however, research on new models of breathing assemblies is lacking. This study compared metabolic gas analysis data from a mouthpiece with a noseclip (MOUTH) and a face mask (MASK). Volunteers (7 males, 7 females; 25.1 ± 2.7 years) completed two maximal treadmill tests within 1 week, one MOUTH and one MASK, in random order. The difference in maximal oxygen consumption (VO2max) between MOUTH (52.7 ± 11.3 ml/kg·min) and MASK (52.2 ± 11.7 ml/kg·min) was not significant (P = 0.53). Likewise, the mean MOUTH-MASK differences in minute ventilation (VE), fraction of expired oxygen (FEO2) and carbon dioxide (FECO2), respiration rate (RR), tidal volume (Vt), heart rate (HR), and rating of perceived exertion (RPE) at maximal and submaximal intensities were not significant (P > 0.05). Furthermore, there was no systematic bias in the error scores (r = -0.13, P = 0.66), and 12 of the 14 participants had a VO2max difference of =3 ml/kg·min between conditions. Finally, there was no clear participant preference for using the MOUTH or MASK. Selection of MOUTH or MASK will not affect the participant`s gas exchange or breathing patterns.